Tekanan darah sistolik, indeks kardiak dan sindrome Eisenmenger merupakan prediktor kematian pada pasien hipertensi arteri pulmonal terkait penyakit jantung bawaan: analisis dari register COHARD-PH - Rochmat, Muflihatul Baroroh; Setianto, Budi Yuli; Anggrahini, Dyah Wulan; Dinarti, Lucia Kris; Hartopo, Anggoro Budi (Jurnal Kardiologi Indonesia, 2024)
Background: Pulmonary arterial hypertension (PAH) is a complication of left-to-right intracardiac shunt congenital heart disease (LtR-shunt CHD). There are several known predictors of mortality in PAH patients, however predictors of mortality in LtR-shunt CHD-associated PAH need to be validated. Objectives: We aimed to investigate the predictors of mortality among adult LtR-shunt CHD-associated PAH patients. Methods: This research was a retrospective cohort study that included adult patients with LtR-shunt CHD-associated PAH retrieved from the COHARD-PH registry. Several baseline variables were selected as potential predictors of mortality, namely (1) clinical data: WHO-functional class, SaO2, 6-min walking distance, systolic blood pressure, and Eisenmenger syndrome; (2) laboratory data: hemoglobin and NT-pro BNP levels; (3) echocardiography data: pericardial effusion, defect size, and TAPSE; and (4) hemodynamic data: right atrial pressure, cardiac output and index, SvO2, and flow ratio. The mortality outcome was assessed from the cohort registry. Results: A total of 124 subjects with LtR-shunt CHD-associated PAH were included. Sixteen subjects (12.9%) died during the follow-up period. The baseline variables which showed significant association with mortality were lower systolic blood pressure, Eisenmenger syndrome, higher NT-pro BNP level, and lower cardiac output. The multivariable analysis showed that systolic blood pressure <100 mmHg (OR 10.99; 95% CI 2.54-47.51, p=0.001), cardiac index <2.5 L/min/m2 (OR 8.13; 95% CI: 1.59-42.28, p=0.011) and Eisenmenger syndrome (OR 3.87; 95%CI: 1.06-14.07) were the independent predictors for mortality. Conclusions: The systolic blood pressure <100 mmHg, cardiac index <2.5 L/min/m2, and Eisenmenger syndrome were independent predictors of mortality among adults with LtR-shunt CHD-associated PAH.